An Exploratory Study on Green Banking Usage in Rural Areas of Tamil Nadu - RAJA, N.; JAGADEESWARI, B. YASODHA (International Journal of Psychosocial Rehabilitation, 2020)
The biggest problem being faced by the whole world is environment management and reducing the damage to the natural resources and global warming. Today, the way we are recklessly consuming resources on earth, the question arises what we will leave for future generation. Thus, it is the responsibility of every individual as well as institutions to contribute for green economy and adds to sustainable development of the economy. The concept of sustainable development that is taking care of the need of present generation without compromising the needs of future generation, has given rise to green marketing and then green banking. Green banking is different from traditional banking, as green banking focus on promoting environment friendly banking. Green banking is also known as ethical banking. Green banking will be mutually beneficial to the customers, banks industries and the economy. Banking industry is the backbone of the financial system of a country. The objective of this paper is to examine the illiteracy of bank customers of rural areas and by designing the model how it will helpful to them while carrying the green banking transactions. The present study is an attempt to understand and appreciate the role of banks in sustainable development through green banking. The data required for the study were collected from both the primary and secondary sources.